2003
DOI: 10.1046/j.1365-2044.2003.02952.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative screening: Criteria for referring to anaesthetists

Abstract: SummaryNurses assess patients pre-operatively using screening questionnaires and locally-developed protocols. Our objectives were to determine which questions might identify patients who should be seen by an anaesthetist before the day of surgery. A review of the literature and a preliminary questionnaire to establish questions to be tested was followed by a modified, two-round Delphi questionnaire to determine the level of agreement by anaesthetists. There was agreement for referring patients who gave a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…10 Preadmission clinics are frequently not staffed by physicians but by nurses who function in a screening role, detecting medical or physical conditions that trigger an anesthesiology or internal medicine consultation. 11,12 Indeed, even in clinics where patients are assessed preoperatively by an anesthesiologist, such as is the case in our clinic, preoperative test orders may not be individualized but rather ordered by the surgical service based on the clinical pathway for the proposed surgical procedure.…”
mentioning
confidence: 99%
“…10 Preadmission clinics are frequently not staffed by physicians but by nurses who function in a screening role, detecting medical or physical conditions that trigger an anesthesiology or internal medicine consultation. 11,12 Indeed, even in clinics where patients are assessed preoperatively by an anesthesiologist, such as is the case in our clinic, preoperative test orders may not be individualized but rather ordered by the surgical service based on the clinical pathway for the proposed surgical procedure.…”
mentioning
confidence: 99%
“…However, much of this work is dominated by medical protocols in order to guarantee medical fitness for surgery (22)(23)(24)(25)(26) . Although such tasks are vital, an unfortunate consequence of such a rapidly changing medical agenda is that evidence based 'nursing knowledge' has contributed very little to the success of day surgery (27) .…”
Section: A Y S U R G E R Y : a N E W E R A O F S U R G I C A L N U mentioning
confidence: 99%
“…However, extended roles and the gaining of pre-assessment skills both embrace devolved medical tasks (23,26,38,(61)(62)(63)(64)(65) . Unfortunately, the exposition of nursing knowledge is again not considered although some studies have demonstrated the value of nursing skills in the pre-assessment clinic (39,66) .…”
Section: E T H O D O L O G Y L I T E R a T U R E R E V I E Wmentioning
confidence: 99%
“…Pre-anesthetic screening questionnaires given by nurses have proven useful in helping to streamline communications between nursing and anesthesia personnel. 12,13 The cooperation of anesthesia colleagues, surgeons, and nurses has been recognized as essential for the proper implementation of fasting guidelines published by the American Society of Anesthesiologists. 14 Patients should not be under "nothing by mouth" (NPO) orders for extended periods of time and may have clear liquids up to 2 to 4 hours preprocedure to maintain their fluid status.…”
Section: Preoperative/preanesthesia Assessmentmentioning
confidence: 99%